Prevalencia de Síndrome Visual Informático por educación virtual en estudiantes de Medicina Humana de la Universidad Nacional de Loja - Poma Poma, José Alejndro (2021)
The COVID-19 pandemic has caused a great impact on the health system and on the lifestyle of the population. Mandatory isolation increased the use of digital technology, with significant repercussions on visual health. In order to determine the prevalence of Informatics Visual Syndrome (IVS) during virtual education, a descriptive, cross study was carried out in 238 students of Human Medicine of the Universidad Nacional de Loja in the period April - September 2021, selected by inclusion and exclusion criteria. The prevalence of IVS was 85.7 %. The main symptoms reported were eye burning (73 %), headache (67.6 %) and back pain (64.2 %). The devices used to receive classes were the computer, used mostly during 7-10 hours (38.7 %), followed by the cell phone used during 3-6 hours in 42.6 % of participants and the tablet, which was used for 1-3 hours in 9.3 %. About 25% of students did not take visual breaks while receiving their classes, and of those who did, most of them did so after more than 2 hours of exposure (33.3 %). Among the mitigating ergonomic measures, artificial tears were used in 33.3 % and eyes were kept closed for short periods of time in 41.2 %; those who did not adopt any measure represented 23 %. Finally, 93.1 % of students perceived an increase in symptoms during this period of virtual education, compared to before the pandemic. Key words: COVID-19, asthenopia, visual disorders, visual ergonomics.